Main differences in osteoporotic fracture models: which should I use?. (January 2016) - Simpson, A. Hamish; Murray, Iain R.
Abstract: Osteoporosis is a global public health problem currently affecting more than 200 million people worldwide. Major research efforts are being made to improve the outcomes for patients with osteoporosis. However, the treatment of fractures associated with osteoporosis remains unsatisfactory. Animal models continue to be an important tool for establishing strategies to treat osteoporotic fractures, and various methods of inducing osteoporosis have been used. Investigators must select a model that best reflects the clinical problem being studied, and the underlying pathophysiology of the osteoporosis in the target patient group. In particular a model for Type I post-menopausal osteoporosis should mimic a fall in oestrogen and rise in osteoclast activity observed with this condition, whereas a model for type II 'senile' osteoporosis should mimic the fall in osteoblast activity. Unfortunately, there is no single all-encompassing model that precisely imitates the underlying osteoporosis or the fracture patterns seen in humans. As such the choice of species and model must be individualised to the scientific question being addressed. This article summarises general considerations when choosing an osteoporotic fracture model and outlines existing models of osteoporosis. The most appropriate model in a range of osteoporotic fracture research scenarios are subsequently considered.